Rising Threat: Long‐Term Trends in the Incidence and Mortality of Thymic Epithelial Tumor - Zishan Chen; Shiwen Liu; Chunting Chen; Jinmang Zhuang; Xinying Xu; Maolin Liu; Fancai Lai; Fei He (Cancer Medicine)
ABSTRACT Introduction An upward trend in the incidence of thymic epithelial tumors (TETs) has been reported over the past few decades, but because of its rarity, little is currently known about its epidemiological trends. This study examined temporal trends in the incidence and mortality of TETs in the US and explored these trends in population subgroups while investigating important factors that influence their prognosis. Methods A retrospective, population‐based study was conducted using nationally representative data from the Surveillance, Epidemiology, and End Results program, and 4979 patients diagnosed with TETs from 2000 to 2020 were evaluated. Associated population data were used to determine age‐adjusted incidence and mortality, and 5‐year TET‐specific mortality (SM). Trends were assessed for the entire cohort, as well as for particular subgroups, including thymoma and thymic carcinoma. Results From 2000 to 2020, the overall incidence and mortality of TETs were 2.769 and 1.203 per million person‐years, respectively. Both the age‐adjusted incidence and mortality of TETs increased over the study period, with increases occurring across almost all ethnic groups, histological subtypes, and stages. Multivariate analysis revealed that age, World Health Organization histological type (B1, B2, and B3 thymoma and thymic carcinoma), Masaoka–Koga stage (IIB and III/IV), maximum tumor diameter (5–10 and > 10 cm), surgery, and chemotherapy were independently associated with TET‐SM. Conclusions The incidence and mortality of TETs have steadily increased over time, and these trends might be related to the widespread use of computed tomography for lung cancer screening and the increasing number of TETs found incidentally. The study also identified several important factors independently associated with TET‐SM, suggesting that early diagnosis and surgical intervention are critical to achieving good prognoses.